covid healing - Riza, Fahru (Institute of Accounting Research and Novation (IARN), 2024)
Exposure to information through online platforms can influence the perceived opinions of the people who read it. This is an assumption often made by some social media observers. However, quantitative measurement in Indonesia is still limited. This study aims to find out how exposure to information on online platforms can influence people's perceptions and opinions. In this case, the research focused on the Kanjuruhan Tragedy case and various information related to this tragedy. This research seeks to identify how news that has negative content (low competence of the authorities, irresponsibility of the PSSI leadership and so on) affects the perception of the football community who read it. In this research we used a case study of Jakmania in Serengseng Sawah.